Association between religious and socio‐economic background of parents of children with solid tumors and DNR orders. Issue 2 (12th August 2013) - Hileli, Inbal; Weyl Ben Arush, Myriam; Hakim, Fahed; Postovsky, Sergey
Abstract Background The influence of socio‐economic and religious background on decisions made by parents of children with incurable cancer regarding DNR orders is not fully understood. Procedure A retrospective analysis of medical charts of patients who died between January 2000 and January 2011 was performed. The following data were sought: written evidence of DNR discussion with parents, religious background, educational level, monthly income. Results There was evidence of a discussion on DNR in 73/90 charts. DNR consent was obtained in 14/17 (82.4%) cases where at least one parent had >15 years of education versus in only 24/45 (53.3%) cases where both parents had ≤15 years education as determined by univariate analysis (P = 0.03). DNR consent was also more likely to be obtained among parents of children with income >10, 000 NIS (24/30, 80.0% vs. 20/38, 52.6%, P = 0.013). Parents of Jewish (22/30, 73.3%), Islamic (16/26, 61.5%), and Christian (8/9, 88.9%) background were equally likely to provide DNR consent. However, Druze families were less likely to do so (2/8, 25.0%, P = 0.036). Conclusions The process of decision‐making to a DNR request was associated with parents' educational level and monthly family income, and not by religious background, with the exception of Druze families. Pediatr Blood Cancer 2014;61:265–268. © 2013 Wiley Periodicals, Inc.